Degradable delivery particles from mixed acid treated chitosan

By treating chitosan with mixed acids and reacting with crosslinking agents to generate the reaction product of chitosan, the problems of non-biodegradation and premature release of microcapsules in the prior art are solved, and delivery particles with high structural integrity and biodegradability are achieved.

CN119790132APending Publication Date: 2025-04-08ENCAPSYS LLC
View PDF 30 Cites 0 Cited by

Patent Information

Application Number
CN202380062904.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-01
Filing Date
2023-11-29
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art is difficult to develop biodegradable microcapsules, and delivery particles used in aqueous compositions have problems with premature release.

Method used

By treating chitosan with a mixture of the first and second acids, acid-treated chitosan is formed and reacted with a crosslinking agent to form a reaction product of chitosan to form delivery particles with high structural integrity.

Benefits of technology

High structural integrity and biodegradability of the delivery particles are achieved, reducing leakage risks and maintaining stability in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005290915490000241
    Figure BDA0005290915490000241
  • Figure BDA0005290915490000242
    Figure BDA0005290915490000242
  • Figure BDA0005290915490000243
    Figure BDA0005290915490000243
Patent Text Reader

Abstract

Improved delivery particles comprising a benefit agent core material and a shell encapsulating the core material are described, as well as methods of forming such delivery particles and articles of manufacture. The shell is the reaction product of a cross-linking agent and an acid-treated chitosan wherein the acid-treated chitosan is treated with a weak acid, or even a mixture of a first acid and a second acid, the first acid comprising a strong acid and the second acid comprising a weak acid. The first acid and the second acid are present in an equivalent concentration ratio of about 20: 80 to about 80: 20. The delivery particles of the present invention have improved release properties, with enhanced degradation properties in the OECD test method 301B.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] Joint Research Statement

[0003] Encapsys, LLC and The Procter & Gamble Company entered into a joint research agreement on or about July 29, 2021, and the invention was made as a result of activities conducted between the parties within the scope of the joint research agreement in effect on or before the date of this invention. Technical Field

[0004] The present invention relates to a method for manufacturing a capsule and a biodegradable delivery particle produced by such a method, the delivery particle comprising a core material and a shell encapsulating the core, the shell comprising a reaction product of a crosslinking agent and mixed acid-treated chitosan. The shell is made of acid-treated chitosan and a crosslinking agent, wherein the acid-treated chitosan is produced by treating chitosan with a mixture of a strong acid and a weak acid. Background Art

[0005] Encapsulation (also referred to as microencapsulation) is a method of encapsulating a droplet of a liquid, a solid particle or a gas in a solid shell and generally within the micrometer range. The core material is separated from the surrounding environment by a shell. Encapsulation technology has a wide range of commercial applications in different industries. In general, capsules can perform one or more of the following: (i) providing stability of formulations or materials via mechanical separation of incompatible components, (ii) protecting the core material from the surrounding environment, (iii) masking or hiding the undesirable properties of active ingredients, and (iv) controlling or triggering the release of active ingredients to a specific time or position. All of these attributes can lead to an increase in the shelf life of several products and the stability of active ingredients in liquid formulations.

[0006] Various processes and exemplary methods and materials for encapsulation are described in Schwantes (U.S. Patent No. 6,592,990), Nagai et al. (U.S. Patent No. 4,708,924), Baker et al. (U.S. Patent No. 4,166,152), Wojciak (U.S. Patent No. 4,093,556), Matsukawa et al. (U.S. Patent No. 3,965,033), Ozono (U.S. Patent No. 4,588,639), Irgarashi et al. (U.S. Patent No. 4,610,927), Brown et al. (U.S. Patent No. 4,552,811), Scher (U.S. Patent No. 4,285,720), Jahns et al. (U.S. Patent Nos. 5,596,051 and 5,292,835), Matson(U.S. Patent No. 3,516,941), Foris et al. (U.S. Patent Nos. 4,001,140, ​​4,087,376, 4,089,802 and 4,100,103), Greene et al. (U.S. Patent Nos. 2,800,458, 2,800,457 and 2,730,456), Clark (U.S. Patent No. 6,531,156), Hoshi et al. (U.S. Patent No. 4,221,710), Hayford (U.S. Patent No. 4,444,699), Hasler et al. (U.S. Patent No. 5,105,823), Stevens (U.S. Patent No. 4,197,346), Riecke (U.S. Patent No. 4,622,267), Greiner et al. (U.S. Patent No. 4,547,429), and Tice et al. (U.S. Pat. No. 5,407,609) et al. and as taught by Herbig in the section entitled "Microencapsulation" in Kirk-Othmer Encyclopedia of Chemical Technology, Vol. 16, pp. 438-463.

[0007] Core-shell encapsulation can be used to preserve active agents (e.g., beneficial agents) in harsh environments and release them at a desired time, which can be during or after use of the article into which the delivery particles are incorporated. Among the various mechanisms that can be used to release beneficial agents from delivery particles, the mechanism that is typically relied upon is mechanical rupture of the capsule shell by friction or pressure. The choice of mechanical rupture as a release mechanism poses another challenge to manufacturers because rupture must occur at a specific desired time, even if the capsule is subjected to mechanical stress before the desired release time.

[0008] Industrial interest in encapsulation technology has led to the development of several polymer capsule chemistries that attempt to meet the requirements of biodegradability, low shell permeability, high deposition, targeted mechanical properties and rupture profiles. Increased environmental concerns have put polymer capsules under scrutiny, so manufacturers have begun to investigate sustainable solutions for the encapsulation of beneficial agents.

[0009] Biodegradable materials exist and can be formed into delivery particles via coacervation, spray drying or phase inversion precipitation. However, delivery particles formed using these materials and techniques are highly porous and are not suitable for aqueous compositions containing surfactants or other carrier materials because the beneficial agent is released prematurely into the composition.

[0010] There are non-leaky and functional delivery particles in surfactant-based aqueous compositions, however due to their chemical nature and cross-linking they are not biodegradable.

[0011] Encapsulation can be found in a variety of fields, such as pharmaceuticals, personal care, textiles, food, coatings and agriculture. In addition, the main challenge faced by encapsulation is the need to completely retain the encapsulated active agent within the capsule throughout the supply chain until the controlled or triggered release of the core material is applied. Especially when it comes to small molecule encapsulation, there are significantly limited microencapsulation technologies that can meet the stringent standards of long-term retention and active protection capabilities for commercial needs.

[0012] Delivery particles having a shell made at least in part from a chitosan-based material are known. However, such particles may not provide the desired level of performance. Furthermore, due to its tendency to increase in viscosity, chitosan can be a challenging material to handle.

[0013] U.S. Patent Publication 2020 / 0252469 discloses treating chitosan in an acidic medium before microcapsule formation, for example by adjusting the pH with hydrochloric acid (HCl). However, there are challenges associated with such treatment methods. For example, under some conditions, hydrochloric acid can be corrosive to manufacturing equipment typically made of steel. Additionally or alternatively, improvements in the performance of delivery particles are still desired.

[0014] There continues to be a need for improved treatment compositions including delivery particles made from sustainable materials, such as chitosan-based materials. There is a need for delivery particles that are biodegradable, based on materials that are not corrosive to manufacturing equipment, and yet have high structural integrity to reduce leakage and resist damage from harsh environments.

[0015] definition

[0016] For ease of reference in this specification and claims, the terms "monomer" or "monomers" as used herein with respect to the structural material forming the wall polymer of the delivery particle are to be understood as monomers, but also include oligomers and / or prepolymers formed from the specified monomers.

[0017] As used herein, the term "water-soluble material" means a material having a solubility in water at 60°C of at least 0.5% by weight.

[0018] As used herein, the term "oil-soluble" means a material having a solubility of at least 0.1 wt. % at 50°C in the core of interest.

[0019] As used herein, the term "oil dispersible" means a material that is dispersible at least 0.1 wt. % in the core of interest at 50°C without visible agglomerates.

[0020] As used herein, "delivery particle," "particle," "encapsulate," "microcapsule," and "capsule" are used interchangeably unless otherwise indicated. As used herein, these terms typically refer to a core / shell delivery particle. Summary of the invention

[0021] The present invention describes delivery particles comprising a core material and a shell encapsulating the core material. The core material may comprise a beneficial agent. The shell comprises a polymer. More particularly, the present invention discloses a composition comprising a core-shell encapsulate population, the core comprising a beneficial agent. The shell is a polymer material, more particularly comprising the reaction product of a crosslinking agent and acid-treated chitosan.

[0022] In the present invention, acid-treated chitosan is produced when chitosan is treated with a mixture of a first acid and a second acid. The first acid comprises a strong acid, and the second acid comprises a weak acid. In the present invention, chitosan is treated with a mixed acid at a pH of 6.5 or less, or even less than pH 6.0, or even a pH of 3-6 and a temperature of at least 25° C. to reduce the viscosity of the chitosan. The chitosan is treated with the mixture for at least one hour or to obtain a chitosan solution viscosity of no more than about 1500 cps, or even no more than 500 cps of the acid-treated chitosan. The first acid and the second acid are present in a normality ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35, wherein the chitosan is treated with the mixture at a pH of 6.5 or less.

[0023] In addition to the composition, the present invention also discloses a method of preparing the composition, which is a core-shell delivery particle population. The core comprises a beneficial agent and the shell comprises a polymeric material that is the reaction product of a crosslinking agent such as an isocyanate monomer, oligomer or prepolymer and acid-treated chitosan.

[0024] The method for preparing the composition of the present invention comprises the following steps:

[0025] forming an aqueous phase by treating chitosan with a mixture of a first acid and a second acid, the first acid comprising a strong acid and the second acid comprising a weak acid, wherein the chitosan is treated at a pH of 6.5 or less, or even less than pH 6.5, or even a pH of 3-6, and at a temperature of at least 25° C. for at least one hour or to achieve a viscosity of less than 1500 centipoise (cp) and preferably less than 500 cp, and wherein the first acid and the second acid are present in a normality ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35, and thereby forming acid-treated chitosan; and

[0026] forming an oil phase comprising dissolving together at least one benefit agent and at least one crosslinking agent, optionally with added oil; and

[0027] forming an emulsion by mixing an aqueous phase and an oil phase in an excess of aqueous phase under high shear agitation, thereby forming droplets of the oil phase dispersed in the aqueous phase, and optionally adjusting the pH of the emulsion to within the range of pH 3 to pH 6; and

[0028] The emulsion is solidified by heating to at least 40°C for a time sufficient to form a shell at the interface of the droplet with the aqueous phase, the shell comprising the reaction product of the crosslinker and the acid-treated chitosan, and the shell surrounding a core comprising droplets of the oil phase. The droplets of the oil phase contain the beneficial agent, either because the beneficial agent is itself an oil or is soluble in the added oil or is soluble in the crosslinker.

[0029] In some embodiments, at least 21% by weight of the shell comprises acid-treated chitosan.

[0030] In other configurations, the delivery particles of the present invention can be made into new articles by incorporating into various manufactured articles. Such articles can be selected from agricultural formulations, slurries encapsulating agricultural active agents, dried encapsulates encapsulating agricultural active agents, agricultural formulations encapsulating pesticides, and agricultural formulations for delivering pre-emergence herbicides. The agricultural active agent can be selected from agricultural herbicides, agricultural pheromones, agricultural pesticides, agricultural nutrients, insect control agents, and plant stimulants. DETAILED DESCRIPTION

[0031] The present invention describes a delivery particle comprising a core material and a shell encapsulating the core material. The core material may comprise a beneficial agent. The shell comprises a polymer.

[0032] The present disclosure relates to treatment compositions comprising delivery particles having a shell, the shell being at least partially made of a chitosan-based material. In particular, the delivery particles include a shell comprising the reaction product of chitosan and a crosslinking agent. The chitosan used to prepare the particle shell is treated with a weak acid, or even a mixture of acids (i.e., a mixture comprising a strong acid and a weak acid), prior to shell formation.

[0033] Typically, when chitosan is dissolved in water, such as during the process of preparing delivery particles, the resulting mixture tends to be very viscous. This can lead to flowability and processing challenges and / or inhibit proper formation of the delivery particle shell. It has been found that acid treatment can lead to a decrease in the viscosity of the mixture. Additionally, it is believed that acid treatment of chitosan can beneficially affect the molecular weight of the chitosan, thereby leading to improved shell formation and / or delivery performance.

[0034] Nevertheless, even when chitosan is processed at a constant pH, it was found that the choice of acid can make a difference. For example, using a strong acid (such as HCl) alone can result in relatively suitable particles, but can lead to potential corrosion problems in manufacturing equipment.

[0035] It has surprisingly been discovered that treating chitosan with a weak acid, or even an acid mixture comprising a weak acid, can result in suitable delivery particles while reducing corrosion challenges to manufacturing equipment.

[0036] It has even been surprisingly discovered that careful selection of an acid (or more precisely, acids) can provide benefits in one or more vectors. For example, it is believed that treating chitosan with a mixed acid system comprising a strong acid and a weak acid (particularly in a certain ratio) results in good performance delivery particles while reducing the risk of corrosion in manufacturing equipment.

[0037] The delivery particle has a shell made at least in part of a chitosan-based material. The shell is a reaction product of a crosslinking agent and acid-treated chitosan. In particular, the delivery particle includes a shell comprising the reaction product of chitosan and the crosslinking agent. Notably, the chitosan is characterized by being treated with a mixture of a first acid and a second acid, the first acid comprising a strong acid and the second acid comprising a weak acid. The combination results in an increase in the average molecular weight of the treated chitosan within a specific range.

[0038] Without wishing to be bound by theory, it is believed that careful selection of the molecular weight of chitosan may be advantageous. For example, selection of chitosan having a molecular weight above a certain threshold may result in delivery particles that perform better at some contact points compared to particles made of chitosan of lower molecular weight. In addition, selection of chitosan characterized by a relatively high molecular weight may result in processing challenges because such chitosan tends to increase viscosity, especially in aqueous environments; relatively high viscosity may affect the convenient flowability of such solutions and / or inhibit the full formation of particle walls. Surprisingly, treatment with the mixed acid taught herein produces chitosan, wherein without wishing to be bound by theory, it is believed that careful selection of the molecular weight of chitosan may be advantageous. For example, selection of chitosan having a molecular weight above a certain threshold may result in delivery particles that perform better at some contact points compared to particles made of chitosan of lower molecular weight. In addition, selection of chitosan characterized by a relatively high molecular weight may result in processing challenges because such chitosan tends to increase viscosity, especially in aqueous environments; relatively high viscosity may affect the convenient flowability of such solutions and / or inhibit the full formation of particle walls. Surprisingly, chitosan is produced by mixed acid treatment as taught herein, wherein the weight average molecular weight increases from about 100kDa to about 300kDa. It was found that the increase is a function of the mixed acid ratio. In addition, as the average weight increases, the viscosity decreases so that it is easy to handle. The present invention can achieve a chitosan solution of 3%, preferably 3.5%, more preferably 4% or higher concentration, thereby achieving a surprising reduction in the concentration measured at the same concentration. The viscosity of chitosan at such concentration is typically in the region of 4000 centipoise (cP). According to the method of the present invention, the chitosan treated with acid at such concentration shows a viscosity reduction of 60% or even more than 60% at the same concentration to 1500cP, or even 1000cP, or even 500cP. To illustrate, chitosan having a typical starting viscosity of 4000 cP at 3.5% concentration exhibits a 60% or even greater reduction in viscosity at the same concentration, to a viscosity of 1500 cP, or even 1000 cP, treated according to the method of the invention.

[0039] The chitosans, delivery particles, treatment compositions and related methods of the present disclosure are discussed in more detail below.

[0040] The present invention teaches compositions comprising core-shell encapsulates (also referred to as delivery particles), including methods of preparing such encapsulates or delivery particles. The core comprises a beneficial agent (preferably a fragrance), and the shell may comprise, for example, a polyurea resin polymer material, which is the reaction product of a crosslinking agent (e.g., a polyisocyanate) and acid-treated chitosan. In forming the composition of the present invention, chitosan is treated with a mixture of a first acid and a second acid, the first acid comprising a strong acid and the second acid comprising a weak acid. Chitosan is treated with the acid mixture for at least one hour at a pH of 6.5 or less, or even less than pH 6.0, or even a pH of 3-6, or even a pH of 3.5 to 6, or even a pH of 4 to 6 and at a temperature of at least 25°C. Typically this treatment step can be measured as a period of time to obtain a chitosan solution having a viscosity of 1500 centipoise, or less than 1500 centipoise (cp) and preferably less than 500 cp.

[0041] Chitosan can be characterized by a weight average molecular weight of about 100kDa-about 600kDa. Preferably, chitosan is characterized by a weight average molecular weight (Mw) of about 100kDa-about 500kDa, preferably about 100kDa-about 400kDa, more preferably about 100kDa-about 300kDa, even more preferably about 100kDa-about 200kDa. The method for determining the molecular weight and related parameters of chitosan is provided in the following test method section and uses gel permeation chromatography (GPC-MALS / RI) technology with multi-angle light scatterer and refractive index detection. Selecting chitosan with a preferred weight average molecular weight can result in a capsule with suitable shell formation and / or desired processability. For clarity, the chitosan weight average molecular weight is measured before being treated with acid as described herein.

[0042] Chitosan preferably used in the material of the present disclosure is acid-treated chitosan. For example, chitosan (which may also be referred to as original chitosan or parent chitosan before acid treatment) may preferably be treated with acid at a temperature of about 25°C to about 99°C, preferably about 75°C to about 95°C, at a pH of 6.5 or less for at least one hour, preferably about one hour to about three hours. Acid may be selected from strong acids (e.g., hydrochloric acid), weak acids (e.g., formic acid or acetic acid), or mixtures thereof. Chitosan may preferably be treated with acid at a pH of 2-6.5, preferably a pH of 3-6, even more preferably a pH of 4-6.

[0043] Acid-treated chitosan can be formed by treating chitosan with a mixture of acids (e.g., a mixed acid system). Preferably, the acid-treated chitosan is produced by treating chitosan with a mixture comprising a first acid and a second acid, wherein the first acid comprises a strong acid and wherein the second acid comprises a weak acid. As described in more detail above, it is believed that the use of a mixture of acids described herein provides delivery particles of appropriate performance while, for example, minimizing risk to manufacturing equipment.

[0044] Chitosan is preferably treated with the mixture at a pH of 6.5 or less, preferably a pH of less than 6.5, more preferably a pH of 3-6, and at a temperature of at least 25° C., preferably about 25° C. to about 99° C., preferably about 75° C. to about 95° C. Too low a temperature may result in an incomplete reaction; too high a temperature may result in undesirable degradation of the chitosan.

[0045] The first acid of the acid mixture and the second acid of the acid mixture are present in an equivalent concentration ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35. In the composition, it is desired that at least 21% by weight of the crust is composed of structural parts derived from acid-treated chitosan. Chitosan can form 21% by weight of the shell or more, and it is found that the resulting shell as described herein is beneficial to the long-term retention and active protection of the beneficial agent, making the delivery particles particularly suitable for commercial needs, especially when it comes to the encapsulation of small molecules as beneficial agents.

[0046] The first acid of the acid mixture is a strong acid selected from the group consisting of hydrochloric acid, perchloric acid, nitric acid, sulfuric acid and even mixtures thereof. The second acid is an organic acid selected from the group consisting of formic acid, acetic acid, ascorbic acid, glutamic acid, lactic acid, maleic acid, malic acid, succinic acid, citric acid, acrylic acid, oxalic acid, tartaric acid and mixtures thereof.

[0047] The first acid can be selected to have a pKa of less than 1, and the second acid pKa is 5.5 or less, preferably a pKa of about 1 to about 5.5. The acid can be monobasic, dibasic or polybasic. It is understood that a dibasic, tribasic or polybasic acid will have more than one ionizable hydrogen, and therefore have a first or initial pKa and additional pKa values ​​for additional ionizable hydrogens, respectively. For purposes of the present invention, when the acid is dibasic or polybasic, the first pKa refers to the first or initial ionizable hydrogen. Unless otherwise stated, when the acid is dibasic, tribasic or polybasic, pKa refers to the first pKa.

[0048] The ratio of crosslinker to acid-treated chitosan is from 79:21 to 10:90, or even from 2:1 to 1:10, or even from 1:1 to 1:7, based on weight.

[0049] The shell may comprise from 1 to 25 wt % of the core-shell encapsulate.

[0050] The crosslinking agent of the composition may comprise a polyisocyanate. The crosslinking agent (which is a polyisocyanate) may be selected from the following: polyisocyanurates of toluene diisocyanate, trimethylolpropane adducts of toluene diisocyanate, trimethylolpropane adducts of xylylene diisocyanate, methylene diphenyl diisocyanate, toluene diisocyanate, tetramethylxylidine diisocyanate, naphthalene-1,5-diisocyanate, and phenylene diisocyanate. This list is illustrative and is not intended to be limiting.

[0051] When formulated according to the teachings of the present invention, the shell degrades by at least 40% or even at least 60% of its mass after at least 60 days when tested according to test method OECD 301 B.

[0052] The core-shell encapsulate has a core to shell ratio of at least 75:25, or even up to 99:1, or even at least 99.5:0.5 by weight.

[0053] The benefit agent is selected from the group consisting of fragrances, flavors, agricultural actives, phase change materials, essential oils, lubricants, colorants, preservatives, antimicrobial actives, antifungal actives, herbicides, antiviral actives, preservative actives, antioxidants, bioactives, deodorants, emollients, moisturizers, exfoliants, UV absorbers, corrosion inhibitors, silicone oils, waxes, bleaching particles, fabric conditioners, malodor reducers, dyes, optical brighteners, antiperspirant actives, and mixtures thereof.

[0054] Also described is a method of preparing a core-shell delivery particle population, the core comprising a beneficial agent, the shell comprising a polyurea resin, the polyurea resin comprising a polymeric material, the polymeric material being the reaction product of a crosslinking agent (e.g., a polyisocyanate) and an acid-treated chitosan. The method comprises forming an aqueous phase by: treating the chitosan with a mixture of a first acid and a second acid, the first acid comprising a strong acid, and the second acid comprising a weak acid, wherein the chitosan is treated at a pH of 6.5 or less, or even less than pH 6.0, or even at a pH of 3-6, and at a temperature of at least 25° C. for at least one hour or to achieve an acid-treated chitosan of a viscosity of less than 1500 centipoise (cp) and preferably less than 500 cp, the first acid and the second acid being present in an equivalent concentration ratio of about 20:80 to about 80:20, preferably about 40:60 to about 60:40, and thereby forming the acid-treated chitosan;

[0055] forming an oil phase, comprising dissolving together at least one benefit agent and at least one crosslinking agent (preferably a polyisocyanate), optionally with added oil;

[0056] forming an emulsion by: mixing an aqueous phase and an oil phase in an excess of aqueous phase under high shear agitation, thereby forming droplets of the oil phase and the benefit agent dispersed in the aqueous phase, and optionally adjusting the pH of the emulsion to within the range of pH 3 to pH 6;

[0057] The emulsion is solidified by heating to at least 40°C for a time sufficient to form a shell at the interface of the droplet with the aqueous phase, the shell comprising the reaction product of the crosslinker and acid treated chitosan, and surrounding a core comprising droplets of the oil phase and benefit agent.

[0058] Unless otherwise stated, all component or composition levels are in reference to the active portion of that component or composition, and are exclusive of impurities (e.g., residual solvents or by-products) that may be present in commercially available sources of such components or compositions.

[0059] shell

[0060] To produce the delivery particles of the present invention, an aqueous phase is prepared that includes an aqueous solution or dispersion of an amine-containing natural material having a free amino moiety. The amine-containing natural material is a bio-based material. Such materials include, for example, chitosan. The amine-containing natural material is dispersed in water. In the case of chitosan, the material is hydrolyzed, thereby protonating at least a portion of the amine groups and promoting dissolution in water. The hydrolysis is performed using heating for a period of time at an acidic pH (e.g., about 5 or 5.5).

[0061] The oil phase is prepared by dissolving an isocyanate such as a trimer of xylylene diisocyanate (XDI) or a polymer of methylene diphenyl diisocyanate (MDI) in oil at 25°C. A diluent (e.g., isopropyl myristate) can be used to adjust the hydrophilicity of the oil phase. The oil phase is then added to the water phase and ground at high speed to obtain a target size. The emulsion is then solidified in one or more heating steps, such as heating to 40°C in 30 minutes and keeping at 40°C for 60 minutes. The time and temperature are approximately. The temperature and time are selected to be sufficient to form and solidify a shell at the interface of the oil phase droplets and the water continuous phase. For example, the emulsion is heated to 85°C in 60 minutes and then kept at 85°C for 360 minutes to solidify the capsule. The slurry is then cooled to room temperature.

[0062] The volume weighted median particle size of delivery particles according to the invention may range from 5 microns to 150 microns, or even from 10 to 50 microns, preferably from 15 to 50 microns.

[0063] The crosslinking agent of the present invention is preferably a polyisocyanate. For the purposes of the present invention, when referring to useful crosslinking agents, reference to polyisocyanates should be understood to include or be isocyanate monomers, isocyanate oligomers, isocyanate prepolymers, or dimers or trimers of aliphatic or aromatic isocyanates. All such monomers, prepolymers, oligomers, or dimers or trimers of aliphatic or aromatic isocyanates are referred to by the term "polyisocyanate" as used herein.

[0064] Cross-linking agent can be aliphatic or aromatic monomer, oligomer or prepolymer, available with two or more isocyanate functional groups.The cross-linking agent of isocyanate type can be selected from aromatic toluene diisocyanate and derivatives thereof (for delivery of the wall formation of particles), or aliphatic monomer, oligomer or prepolymer, such as hexamethylene diisocyanate and dimer or trimer thereof, or 3,3,5-trimethyl-5-isocyanatomethyl-1-isocyanatocyclohexane tetramethylene diisocyanate.Polyisocyanates can be selected from 1,3-diisocyanato-2-methylbenzene, hydrogenated MDI, bis(4-isocyanatocyclohexyl)methane, dicyclohexylmethane-4,4'-diisocyanate and their oligomers and prepolymers.This list is illustrative and is not intended to limit the polyisocyanates available in the present invention.

[0065] Isocyanates useful in the present invention include isocyanate monomers, oligomers or prepolymers having at least two isocyanate groups, or dimers or trimers thereof. Optimized crosslinking can be achieved with isocyanates having at least three functional groups.

[0066] For the purposes of the present invention, crosslinking agents are understood to include, by way of illustration and not limitation, any isocyanate monomer, oligomer, prepolymer or polymer having at least two isocyanate groups in the monomer, oligomer or prepolymer and containing an aliphatic or aromatic moiety. If aromatic, the aromatic moiety may contain a phenyl, toluyl, xylyl, naphthyl or diphenyl moiety, more preferably a toluyl or xylyl moiety. Aromatic polyisocyanates are understood to be polyisocyanates containing at least one aromatic moiety. For the purposes of the present invention, aromatic polyisocyanates may include diisocyanate derivatives, such as biuret and polyisocyanurate. When aromatic, the polyisocyanate may be, but is not limited to, methylene diphenyl diisocyanate, toluene diisocyanate, tetramethylxylidine diisocyanate, polyisocyanurate of toluene diisocyanate (which may be referred to under the trade name RC is commercially available from Bayer), naphthalene-1,5-diisocyanate, phenylene diisocyanate, 2,2'-methylene diphenyl diisocyanate, 4,4'-methylene diphenyl diisocyanate, 2,4'-methylene diphenyl diisocyanate, tetramethylxylidine diisocyanate, naphthalene-1,5-diisocyanate, 1,4-phenylene diisocyanate, 1,3-diisocyanatobenzene, trimethylolpropane adduct of xylylene diisocyanate (available under the trade name D-110N is commercially available from Mitsui Chemicals), and combinations thereof.

[0067] Aliphatic isocyanates are understood to be monomeric, oligomeric, prepolymeric or polymeric polyisocyanates that do not contain any aromatic moieties. Aromatic polyisocyanates are understood to be polyisocyanates that contain at least one aromatic moiety. Aromatic polyisocyanates are preferred, however, aliphatic polyisocyanates and blends thereof are useful. Aliphatic polyisocyanates include trimers of hexamethylene diisocyanate, trimethylolpropane adducts of toluene diisocyanate (available under the trade name L75 is commercially available from Bayer), the trimer of isophorone diisocyanate, the trimethylolpropane adduct of hexamethylene diisocyanate (available from Mitsui Chemicals), or the biuret of hexamethylene diisocyanate (available under the trade name N 100 is commercially available from Bayer).

[0068] The capsule shell may also be strengthened using additional co-crosslinkers such as multifunctional amines and / or polyamines, for example diethylenetriamine (DETA), polyethyleneimine and polyethyleneamine.

[0069] The shell may also be reinforced using additional co-crosslinkers such as multifunctional amines and / or polyamines, such as diethylenetriamine (DETA), polyethyleneimine, polyvinylamine or mixtures thereof. For example, acrylates may also be used as additional co-crosslinkers to reinforce the shell.

[0070] The polymer material may be formed in a reaction wherein the weight ratio of chitosan present in the reaction to the cross-linking agent present in the reaction is from about 1:10 to about 1:0.1. It is believed that selecting a desired ratio of biopolymer to cross-linking agent can provide desired ductility benefits as well as improved biodegradability. It may be preferred that at least 21% by weight of the shell is composed of moieties derived from chitosan, preferably derived from acid-treated chitosan. The chitosan may be from about 21% to about 95% of the shell in terms of weight percentage of the shell. The ratio of chitosan in the aqueous phase to isocyanate in the oil phase may be from 21:79 to 90:10, or even 1:2 to 10:1, or even 1:1 to 7:1, based on weight. The shell may comprise chitosan at a level of 21 wt% or even greater, preferably about 21 wt% to about 90 wt%, or even 21 wt% to 85 wt%, or even 21 wt% to 75 wt%, or 21 wt% to 55 wt% of the total shell is chitosan. The chitosan of this paragraph may preferably be acid treated chitosan.

[0071] The delivery particle population can be made according to a method comprising the following steps: (a) forming an aqueous phase by treating chitosan with a mixture of a first acid and a second acid, the first acid comprising a strong acid and the second acid comprising a weak acid, wherein the chitosan is treated at a pH of 6.5 or less, or even less than pH 6.5, or even a pH of 3-6 and a temperature of at least 25°C for at least one hour, preferably one hour to three hours; (b) forming an oil phase comprising dissolving together at least one beneficial agent and at least one crosslinking agent (preferably a polyisocyanate), optionally with added oil (e.g., a partitioning modifier) ​​and / or solvent; (c) forming an emulsion by mixing the aqueous phase and the oil phase in an excess of the aqueous phase under high shear agitation, thereby forming droplets of the oil phase (which comprises the beneficial agent) dispersed in the aqueous phase, and optionally adjusting the pH of the emulsion to pH 2-pH 6; (d) curing the emulsion by heating to at least 40°C for a time sufficient to form a shell at the interface of the droplet with the aqueous phase, the shell comprising the reaction product of the crosslinking agent and the acid-treated chitosan, and the shell surrounding the core comprising the beneficial agent.

[0072] Chitosan can be added to water in a jacketed reactor and at a pH from 2 or even from 3 to 6.5, using strong acid (e.g., concentrated HCl) and weak acid (e.g., formic acid or acetic acid) to adjust. The chitosan of this mixture can be acid treated by heating to an elevated temperature (e.g., 85°C) within 60 minutes, and then can be kept at this temperature for 1 minute to 1440 minutes or longer. The aqueous phase can then be cooled to 25°C. Optionally, deacetylation can also be further promoted or enhanced by enzymes to depolymerize or deacetylate chitosan. The oil phase can be prepared by dissolving an isocyanate such as a trimer of xylene diisocyanate (XDI) or a polymer of methylene diphenyl diisocyanate (MDI) in oil at 25°C. A diluent (e.g., isopropyl myristate) can be used to adjust the hydrophobicity of the oil phase. The oil phase can then be added to the aqueous phase and ground at high speed to obtain a target size. The emulsion may then be cured in one or more heating steps, such as heating to 40°C in 30 minutes and holding at 40°C for 60 minutes. The time and temperature are approximate. The temperature and time are selected to be sufficient to form and cure the shell at the interface of the oil phase droplets and the aqueous continuous phase. For example, the emulsion may be heated to 85°C in 60 minutes and then held at 85°C for 360 minutes to cure the particles. The slurry may then be cooled to room temperature.

[0073] The shell may degrade by at least 50% after 20 days (or less) when tested according to test method OECD 301B. The shell may degrade by at least 60% of its mass after 60 days (or less) when tested according to test method OECD 301B. The shell may preferably degrade by at least 60% of its mass after 60 days (or less) when tested according to test method OECD 301B. The shell may degrade by 30-100%, preferably 40-100%, 50-100%, 60-100%, or 60-95% within 60 days, preferably 50 days, more preferably 40 days, more preferably 28 days, more preferably 14 days.

[0074] The delivery particles of the present disclosure include a core. The core includes a beneficial agent. The core optionally includes a partitioning modifier.

[0075] The core of the particle is surrounded by a shell. When the shell breaks, the beneficial agent in the core is released. Additionally or alternatively, the beneficial agent in the core can diffuse out of the particle and / or it can be extruded. Suitable beneficial agents in the core can include beneficial agents that provide benefits to the surface.

[0076] core

[0077] The core may comprise from about 5% to about 100% of a benefit agent, which may preferably comprise a fragrance, based on the weight of the core. The core may comprise from about 45% to about 95%, preferably from about 50% to about 80%, more preferably from about 50% to about 70% of a benefit agent, which may preferably comprise a fragrance, based on the weight of the core.

[0078] The benefit agent may include an aldehyde-containing benefit agent, a ketone-containing benefit agent, or a combination thereof. Such benefit agents (e.g., aldehyde-containing or ketone-containing fragrance raw materials) are known to provide preferred benefits, such as freshness benefits. The benefit agent may include at least about 20%, preferably at least about 25%, more preferably at least about 40%, even more preferably at least about 50% of an aldehyde-containing benefit agent, a ketone-containing benefit agent, or a combination thereof, based on the weight of the benefit agent.

[0079] The benefit agent may be a hydrophobic benefit agent. Such agents are compatible with the oil phase typically used in preparing the delivery particles of the present disclosure.

[0080] The benefit agent in the core preferably comprises a fragrance material (or simply "fragrance"), which may include one or more perfume raw materials. Fragrances are particularly suitable for encapsulation in the delivery particles described herein, because the particles containing fragrances can provide freshness benefits across multiple contact points.

[0081] As used herein, the term "fragrance raw material" (or "PRM") refers to a compound having a molecular weight of at least about 100 g / mol and which can be used alone or with other fragrance raw materials to impart an odor, flavor, flavor or aroma. Typical PRMs include alcohols, ketones, aldehydes, esters, ethers, nitrites, and alkenes, such as terpenes. Lists of common PRMs can be found in various reference sources, such as "Perfume and Flavor Chemicals", Volumes I and II; Steffen Arctander Allured Pub. Co. (1994) and "Perfumes: Art, Science and Technology", Miller, PM and Lamparsky, D., Blackie Academic and Professional (1994).

[0082] PRMs can be characterized by their boiling point (BP) measured at atmospheric pressure (760 mm Hg) and their octanol / water partition coefficient (P), which can be described as logP, determined according to the following test method. Based on these characteristics, PRMs can be classified as Quadrant I, Quadrant II, Quadrant III or Quadrant IV fragrances, as described in more detail in U.S. Pat. No. 6,869,923. Suitable Quadrant I, II, III and IV fragrance raw materials are disclosed herein.

[0083] Fragrance raw materials having a boiling point BP below about 250°C and a logP below about 3 are referred to as Quadrant I fragrance raw materials. Quadrant I fragrance raw materials are preferably limited to less than 30% of the aroma materials.

[0084] The aroma may comprise a fragrance raw material having a logP of about 2.5 to about 4. It is understood that other fragrance raw materials may also be present in the aroma.

[0085] The delivery particles of the present invention include beneficial agents, which include one or more compositions intended to be encapsulated. Beneficial agents are selected from many different materials, such as chromogens and dyes, flavoring agents, spices, sweeteners, fragrances, oils, fats, pigments, cleaning oils, medicines, medicinal oils, perfume oils, mold inhibitors, antimicrobial agents, fungicides, bactericides, disinfectants, adhesives, phase change materials, odorants, fertilizers, nutrients and herbicides: as an illustration and not as a limitation. Beneficial agent and oil constitute the core. The core can be liquid or solid. For a core that is solid at ambient temperature, the wall material can be usefully wrapped with less than the entire core for some applications, such as in applications, the availability of the desired agglomerate core. Such purposes can include odor release, cleaning compositions, emollients, cosmetic delivery, etc. When the encapsulant core is a phase change material, uses may include such encapsulated materials in mattresses, pillows, bedding, textiles, athletic equipment, medical devices, building products, construction products, HVAC, renewable energy, apparel, athletic surfaces, electronics, automotive, aviation, footwear, beauty care, laundry, and solar energy.

[0086] The core constitutes the material that is delivered particle encapsulated. Typically, particularly when the core material is a liquid material, the core material and the composition of the inner wall of the delivery particle or one or more combinations of the solvent for the beneficial agent or the distribution modifier. If the core material can play the role of an oil solvent in the capsule, such as serving as a solvent or carrier of a wall-forming material or beneficial agent, the core material can be made to become the main material to be encapsulated, or if the carrier itself is a beneficial agent, it can be the whole material to be encapsulated. However, often, the beneficial agent is 0.01-99 weight percent of the capsule internal content, preferably 0.01-about 65 weight % of the capsule internal content, and more preferably 0.1-about 45 weight % of the capsule internal content. For some applications, even if only trace amounts, the core material can also be effective.

[0087] When the benefit agent itself is not sufficient to act as an oil phase or solvent, particularly for wall-forming materials, the oil phase may comprise a suitable carrier and / or solvent, i.e., an added oil. In this sense, the oil is optional, since the benefit agent itself may sometimes be an oil. These carriers or solvents are typically oils, preferably having a boiling point greater than about 80° C. and having low volatility and being non-flammable. Although not limited thereto, they preferably comprise one or more esters, preferably having a chain length of up to 18 carbon atoms or even up to 42 carbon atoms and / or triglycerides such as esters of C6-C12 fatty acids and glycerol. Exemplary carriers and solvents include, but are not limited to, ethyl diphenylmethane; isopropyl diphenylethane; butyl diphenylethane; benzyl xylene; alkyl biphenyls, such as propyl biphenyl and butyl biphenyl; dialkyl phthalates, such as dibutyl phthalate, dioctyl phthalate, dinonyl phthalate, and ditridecyl phthalate; 2,2,4-trimethyl-1,3-pentanediol diisobutyrate; alkyl benzenes, such as dodecylbenzene; alkyl or aralkyl benzoates, such as benzyl benzoate; diaryl ethers; di(aralkyl) ethers and aryl aralkyl ethers; ethers, such as diphenyl ether , dibenzyl ether and phenylbenzyl ether; liquid higher alkyl ketones (having at least 9 carbon atoms); alkyl or aralkyl benzoates, such as benzyl benzoate; alkylated naphthalenes, such as dipropylnaphthalene; partially hydrogenated terphenyls; high boiling point straight or branched chain hydrocarbons; alkylaryl hydrocarbons, such as toluene; vegetable oils and other crop oils, such as rapeseed oil, soybean oil, corn oil, sunflower oil, cottonseed oil, lemon oil, olive oil and pine oil; methyl esters of fatty acids derived from the transesterification of vegetable oils and other crop oils, methyl esters of oleic acid, esters of vegetable oils, such as soybean methyl esters, straight chain paraffin aliphatic hydrocarbons and mixtures of the foregoing.

[0088] Useful benefit agents include fragrance raw materials such as alcohols, ketones, aldehydes, esters, ethers, nitriles, olefins, fragrances, fragrance solubilizers, essential oils, phase change materials, lubricants, colorants, coolants, preservatives, antimicrobial or antifungal actives, herbicides, antiviral actives, preservative actives, antioxidants, bioactives, deodorants, emollients, moisturizers, exfoliants, UV absorbers, self-repairing compositions, corrosion inhibitors, sunscreens, silicone oils, waxes, hydrocarbons, higher fatty acids, essential oils, lipids, skin coolants, vitamins, sunscreens, antioxidants, glycerin, catalysts, bleaching particles, silica particles, odor reducing agents, dyes, whitening agents, antibacterial actives, antiperspirant actives, cationic polymers, and mixtures thereof. By way of illustration and not limitation, phase change materials useful as beneficial agents may include alkanes having 13-28 carbon atoms, various hydrocarbons such as n-octacosane, n-heptacosane, n-hexacosane, n-pentacosane, n-tetracosane, n-tricosane, n-docosane, n-heneicosane, n-eicosane, n-nonadecane, octadecane, n-heptadecane, n-hexadecane, n-pentadecane, n-tetradecane, n-tridecane. The phase change material may alternatively optionally further include crystalline materials such as 2,2-dimethyl-1,3-propanediol, 2-hydroxymethyl-2-methyl-1,3-propanediol, acids of linear or branched hydrocarbons such as eicosanoic acid and esters such as methyl palmitate, fatty alcohols, and mixtures thereof.

[0089] Preferably, in the case of a fragrance, the fragrance oil acts as both the benefit agent and the solvent for the wall forming material, as illustrated in the Examples herein.

[0090] Optionally, the aqueous phase may include an emulsifier. Non-limiting examples of emulsifiers include the following water-soluble salts: alkyl sulfates, alkyl ether sulfates, alkyl isothionates, alkyl carboxylates, alkyl sulfosuccinates, alkyl succinamates, alkyl sulfates such as sodium lauryl sulfate, alkyl sarcosinates, alkyl derivatives of protein hydrolysates, acyl aspartates, alkyl or alkyl ether or alkyl aryl ether phosphates, sodium lauryl sulfate, phosphatides or lecithin, or stearic acid soaps, sodium stearate, potassium stearate or ammonium stearate, oleate or palmitate, alkyl aryl sulfonates such as sodium dodecylbenzene sulfonate, dialkyl sodium sulfosuccinate, dioctyl sodium sulfosuccinate, dilauryl sodium sulfosuccinate, poly(styrene sulfonate) poly(styrene sulfonate), isobutylene-maleic anhydride copolymer, gum arabic, sodium alginate, carboxymethyl cellulose, cellulose sulfate and pectin, poly(styrene sulfonate), isobutylene-maleic anhydride copolymer, carrageenan, sodium alginate, pectic acid, tragacanth, almond gum and agar; semisynthetic polymers such as carboxymethyl cellulose, sulfated cellulose, sulfated methyl cellulose, carboxymethyl starch, phosphorylated starch, lignin sulfonic acid; and synthetic polymers such as maleic anhydride copolymers (including hydrolyzates thereof), polyacrylic acid, polymethacrylic acid, acrylic acid butyl ester copolymer or crotonic acid homopolymers and copolymers, vinylbenzenesulfonic acid or 2-acrylamido-2-methylpropanesulfonic acid homopolymers and copolymers, and partial amides of such polymers and copolymers amide) or partial esters, carboxyl-modified polyvinyl alcohol, sulfonic acid-modified polyvinyl alcohol and phosphoric acid-modified polyvinyl alcohol, phosphated or sulfated tristyrylphenol ethoxylate, palmitamidopropyltrimonium chloride (Varisoft PATC TM, available from Degussa Evonik, Essen, Germany), distearyl dimonium chloride, cetyltrimethylammonium chloride, quaternary ammonium compounds, fatty amines, aliphatic ammonium halides, alkyldimethylbenzylammonium halides, alkyldimethylethylammonium halides, polyethyleneimine, poly(2-dimethylaminoethyl methacrylate) methyl chloride quaternary salt, poly(l-vinylpyrrolidone-co-2-dimethylaminoethyl methacrylate), poly(acrylamide-co-diallyldimethylammonium chloride), poly(allylamine), quaternized poly[bis(2-chloroethyl)ether-alt-1,3-bis[3-(dimethylamino)propyl]urea] and poly(dimethylamine-co-epichlorohydrin-co-ethylenediamine), condensation products of aliphatic amines with alkylene oxides, quaternary ammonium compounds with long-chain aliphatic groups, For example, distearyl dichloride, and fatty amines, alkyl dimethyl benzyl ammonium halides, alkyl dimethyl ethyl ammonium halides, polyalkylene glycol ethers, condensation products of alkylphenols, aliphatic alcohols or fatty acids with alkylene oxides, ethoxylated alkylphenols, ethoxylated arylphenols, ethoxylated polyarylphenols, carboxylates solubilized with polyols, polyvinyl alcohol, polyvinyl acetate, or copolymers of polyvinyl alcohol polyvinyl acetate, polyacrylamide, poly(N-isopropylacrylamide), poly(2-hydroxypropyl methacrylate), poly(-ethyl-2-oxazoline), poly(2-isopropenyl-2-oxazoline-co-methyl methacrylate), poly(methyl vinyl ether), and polyvinyl alcohol-co-ethylene), and cocamidopropyl betaine. Emulsifiers, if used, are typically present in an amount of about 0.1-40% by weight, preferably 0.2 to about 15% by weight, more typically 0.5 to 10% by weight, based on the total weight of the formulation.

[0091] In addition to the beneficial agent, the delivery particle may also encapsulate a partitioning modifier. Non-limiting examples of partitioning modifiers include isopropyl myristate, C4-C 24 Monoesters, diesters and triesters of fatty acids, castor oil, mineral oil, soybean oil, hexadecanoic acid, methyl ester isododecane, isoparaffin oil, polydimethylsiloxane, brominated vegetable oil and combinations thereof. The delivery particles can also have different ratios of distribution modifiers and beneficial agents to prepare different delivery particle populations that can have different bloom patterns. Such a population can also incorporate different fragrance oils to prepare delivery particle populations that display different bloom patterns and different odor experiences. Patent publication US 2011-0268802 discloses other non-limiting examples of delivery particles and distribution modifiers and is incorporated herein by reference.

[0092] Optionally, if desired, the delivery particles can be dehydrated, for example by decantation, filtration, centrifugation or other separation techniques. Alternatively, the aqueous slurry delivery particles can be spray dried.

[0093] In some examples of the method and composition, the delivery particles may be composed of one or more different groups. The composition may have at least two different delivery particle groups, which are different in terms of the exact composition of the fragrance oil and the median particle size and / or the distribution modifier and the fragrance oil (PM:PO) weight ratio. In some examples, the composition includes more than two different groups, which are different in terms of the exact composition of the fragrance oil and its burst strength. In some other examples, the delivery particle group may be different in terms of the weight ratio of the distribution modifier and the fragrance oil. In some examples, the composition may include a first delivery particle group with a first ratio and a second delivery particle group with a second ratio, the first ratio being 2:3 to 3:2 for the weight ratio of the distribution modifier and the first fragrance oil, and the second ratio being less than 2:3 but greater than 0 for the weight ratio of the distribution modifier and the second fragrance oil.

[0094] In some embodiments, each different delivery particle population can be prepared in a different slurry. For example, a first delivery particle population can be included in a first slurry and a second delivery particle population can be included in a second slurry. It is understood that there is no limit to the number of different slurries used in combination, and the formulator's choice allows for the combination of 3, 10, or 15 different slurries. The first and second delivery particle populations can differ in the exact composition of the benefit agent (e.g., fragrance oil) and in the median particle size and / or PM:PO weight ratio.

[0095] In some embodiments, the composition can be prepared by combining the first and second slurries with at least one auxiliary component, and optionally packaged in a container. In some instances, the first and second delivery particle groups can be prepared in different slurries, and then spray-dried to form particulate matter. Different slurries can be combined before spray drying, or spray-dried separately and then combined together when in the form of a particulate powder. Once in powder form, the first and second delivery particle groups can be combined with auxiliary components to form a composition that can be used as a raw material for manufacturing consumer goods, industrial products, medical products or other commodities. In some instances, at least one delivery particle group is spray-dried and combined with a slurry of the second delivery particle group. In some instances, at least one delivery particle group is dried and prepared by spray drying, fluidized bed drying, tray drying or other such drying methods available.

[0096] In some examples, the slurry or dry particulate matter may include one or more auxiliary materials, such as processing aids selected from the following: carriers, aggregation-inhibiting materials, deposition aids, particle suspension polymers, and mixtures thereof. Non-limiting examples of aggregation-inhibiting materials include salts that can have a charge shielding effect around the particles, such as magnesium chloride, calcium chloride, magnesium bromide, magnesium sulfate, and mixtures thereof. Non-limiting examples of particle suspension polymers include polymers such as xanthan gum, carrageenan, guar gum, shellac, alginates / esters, chitosan; cellulosic materials such as carboxymethyl cellulose, hydroxypropyl methylcellulose, cationically charged cellulosic materials; polyacrylic acid; polyvinyl alcohol; hydrogenated castor oil; ethylene glycol distearate; and mixtures thereof.

[0097] In some embodiments, the slurry may include one or more processing aids selected from water, aggregation inhibiting materials such as divalent salts; particle suspending polymers such as xanthan gum, guar gum, carboxymethyl cellulose.

[0098] In other examples of the present invention, the slurry may include one or more carriers selected from the following: polar solvents, including but not limited to water, ethylene glycol, propylene glycol, polyethylene glycol, glycerol; non-polar solvents, including but not limited to mineral oil, fragrance raw materials, silicone oil, hydrocarbon paraffin oil, and mixtures thereof.

[0099] In some examples, the slurry may include a deposition aid, which may include a polymer selected from the group consisting of: polysaccharides, in one aspect, cationically modified starch and / or cationically modified guar gum; polysiloxanes; polydiallyldimethylammonium halides; copolymers of polydiallyldimethylammonium chloride and polyvinyl pyrrolidone; compositions comprising polyethylene glycol and polyvinyl pyrrolidone; acrylamide; imidazole; imidazolinium halides; polyvinylamine; copolymers of polyvinylamine and N-vinyl formamide; polyvinyl formamide, polyvinyl alcohol; polyvinyl alcohol cross-linked with boric acid; polyacrylic acid; polyglyceryl ether silicone cross-polymers; copolymers of polyacrylic acid, polyacrylate, polyvinylamine and polyvinyl alcohol; low molecular weight amines; Polymers, in one aspect diethylenetriamine, ethylenediamine, bis(3-aminopropyl)piperazine, N,N-bis-(3-aminopropyl)methylamine, tris(2-aminoethyl)amine and mixtures thereof; polyethyleneimine, derivatized polyethyleneimine, in one aspect ethoxylated polyethyleneimine; polymer compounds comprising at least two moieties selected from the group consisting of carboxylic acid moieties, amine moieties, hydroxyl moieties and nitrile moieties on the backbone of polybutadiene, polyisoprene, polybutadiene / styrene, polybutadiene / acrylonitrile, carboxyl-terminated polybutadiene / acrylonitrile or combinations thereof; preformed coacervates of anionic surfactants in combination with cationic polymers; polyamines and mixtures thereof.

[0100] In some additional examples illustrating the present invention, at least one population of delivery particles may be contained in an agglomerate and then combined with a different population of delivery particles and at least one auxiliary material. The agglomerate may include a material selected from the group consisting of silicon dioxide, citric acid, sodium carbonate, sodium sulfate, sodium chloride, and a binder such as sodium silicate, modified cellulose, polyethylene glycol, polyacrylate, polyacrylic acid, zeolite, and mixtures thereof.

[0101] Suitable equipment for use in the methods disclosed herein may include continuous stirred tank reactors, homogenizers, turbine agitators, recirculation pumps, paddle mixers, plow shear mixers, ribbon blenders, longitudinal axis granulators and drum mixers (both in batch and (when applicable) continuous process configurations), spray dryers and extruders. Such equipment can be obtained from Lodige GmbH (Paderborn, Germany), Littleford Day, Inc. (Florence, Kentucky, USA), Forberg AS (Larvik, Norway), Glatt Ingenieurtechnik GmbH (Weimar, Germany), Niro (Soeborg, Denmark), Hosokawa Bepex Corp. (Minneapolis, Minnesota, USA), Arde Barinco (New Jersey, USA).

[0102] Test Method

[0103] It is understood that the test methods disclosed in the Test Methods section of this application should be used to determine the various values ​​of the parameters of applicant's claimed subject matter as claimed and described herein.

[0104] Determination of molecular weight and related parameters of polymers

[0105] The following method describes gel permeation chromatography with multi-angle light scatterer and refractive index detection (GPC-MALS / RI) used to study molecular weight distribution measurements and related values ​​for the polymers described herein.

[0106] Gel Permeation Chromatography (GPC) with Multi-angle Light Scattering (MALS) and Refractive Index (RI) detection (GPC-MALS / RI) allows the absolute molecular weight of polymers to be measured without the need for column calibration methods or standards. The GPC system allows molecules to be separated according to their molecular size. MALS and RI allow information on number average (Mn) and weight average (Mw) molecular weights to be obtained.

[0107] The Mw distribution of water-soluble polymers such as chitosan is typically measured by using a liquid chromatography system (e.g., Agilent 1260 Infinity pump system with OpenLab Chemstation software, Agilent Technology, Santa Clara, CA, USA) and a column set (e.g., 2 Tosoh TSKgel G6000WP 7.8×300mm 13um pore size, guard column A0022 6mm×40mm PW xl-cp, King of Prussia, PA) operating at 40°C. The mobile phase is 0.1 M sodium nitrate in water containing 0.02% sodium azide and 0.2% acetic acid. The mobile phase solvent is pumped isocratically at a flow rate of 1 mL / min. The column was prepared using a Wyatt Multi-angle light scattering (18-angle MALS) detector controlled by software v8.0 and a differential refractive index (RI) detector (Wyatt Technology of Santa Barbara, California, USA).

[0108] Samples were typically prepared at room temperature by dissolving chitosan material at ~1 mg / ml in the mobile phase and hydrated by mixing the solution overnight. Samples were filtered through a 0.8 μm Versapor membrane filter (PALL, Life Sciences, New York, USA) using a 3-ml syringe into an LC autosampler vial prior to GPC analysis.

[0109] The dn / dc value (differential change of refractive index with concentration, 0.15) was used for number average molecular weight (Mn), weight average molecular weight (Mw), Z average molecular weight (Mz), peak maximum molecular weight (Mp) and polydispersity (Mw / Mn) determinations by the Astra detector software.

[0110] An illustrative example of these points on a hypothetical graph of the molecular weight distribution of a polymer is shown in FIG. 1 , where: Mn is indicated by structure number 1 ; Mp is indicated by structure number 2 ; Mw is indicated by structure number 3 ; and Mz is indicated by structure number 4 .

[0111] Viscosity

[0112] The viscosity of the liquid finished product was measured using an AR 550 rheometer / viscometer from TA instruments (New Castle, DE, USA) using parallel steel plates with a diameter of 40 mm and a gap size of 500 μm. The viscosity of the liquid finished product was measured from 0.01 s to 100 s at 21 °C within 3 minutes. -1Up to 25s -1 The logarithmic shear rate scan was acquired for 20 s -1 High shear viscosity and 0.05s -1 Low shear viscosity.

[0113] Test Methods for Determining logP

[0114] The log value of the octanol / water partition coefficient (logP) is calculated for each material tested (e.g., each PRM in a fragrance mixture). The logP of individual materials (e.g., PRMs) is calculated using the Consensus logP calculation model, version 14.02 (Linux), available from Advanced Chemistry Development Inc. (ACD / Labs) (Toronto, Canada) to provide dimensionless logP values. The Consensus logP calculation model from ACD / Labs is part of the ACD / Labs model suite.

[0115] Volume-weighted particle size and size distribution

[0116] Volume weighted particle size distribution was determined via single particle optical sensing (SPOS) (also known as optical particle counting (OPC)) using an AccuSizer 780AD instrument and accompanying software CW788 version 1.82 (Part icle Sizing Systems, Santa Barbara, California, USA) or equivalent. The instrument was configured to the following conditions and options: flow rate = 1 ml / sec; lower size threshold = 0.50 μm; sensor model = sensor model = LE400-05 or equivalent; automatic dilution = on; collection time = 60 seconds; number of channels = 512; container flow volume = 50 ml; maximum consistency = 9200. The measurement was started by placing the sensor in a cold state by flushing with water until the background count was less than 100. The delivery capsule sample in the suspension was introduced and the density of its capsule was adjusted with DI water via automatic dilution, if necessary, to produce a capsule count of at least 9200 / ml. The suspension was analyzed during a time period of 60 seconds. The resulting volume-weighted PSD data is plotted and recorded, and the desired volume-weighted particle size value (eg, median / 50th percentile, 5th percentile, and / or 90th percentile) is determined.

[0117] Procedure for determining % degradation

[0118] The % degradation was determined by the "OECD Guideline for Testing Chemicals" 301B CO2 Release (Modified Sturm Test), adopted on July 17, 1992. For ease of reference, this test method is referred to herein as Test Method OECD 301B.

[0119] Procedure for determination of free oil

[0120] This method measures the amount of oil in the aqueous phase and uses 1 mg / ml dibutyl phthalate (DBP) / hexane as an internal standard solution.

[0121] Slightly more than 250 mg of DBP was weighed into a small beaker and transferred to a 250 ml container. Rinse the beaker thoroughly. Fill to 250 ml with hexane.

[0122] Sample preparation: About 1.5-2 grams (40 drops) of capsule slurry was weighed into a 20 ml scintillation vial and 10 ml of ISTD solution was added and the cap was tightly closed. After vigorous shaking several times within 30 minutes, the solution was pipetted into an autosampler vial and analyzed by GC.

[0123] Additional details. Instrument: HP5890 GC connected to HP Chem Station software; Column: 5m x 0.32 mm id with 1 μm DB-1 liquid phase; Temperature 50°C; hold for 1 minute then heat to 320°C; at 15 degrees / min; Injector: 275°C; Detector: 325°C; 2 ul injection.

[0124] Calculation: For both samples and calibration, add the total peak areas minus the area of ​​DBP.

[0125] i) Calculate mg of free core oil:

[0126]

[0127] ii) Calculate free core oil %

[0128]

[0129] Procedure for Beneficial Agent Leakage Determination

[0130] Obtain 2 one gram samples of the benefit agent granule composition. Add 1 gram (Sample 1) of the granule composition to 99 grams of the product base (where the granules will be used). Age the product base (Sample 1) containing the granules at 35°C in a sealed glass jar for 2 weeks. Similarly age another one gram sample (Sample 2).

[0131] After 2 weeks, filtration was used to recover particles of the granular composition from the product matrix (Sample 1) and from the granular composition (Sample 2). Each granular sample was treated with a solvent that would extract all of the beneficial agent from each sample particle. The solvent containing the beneficial agent from each sample was injected into a gas chromatograph and the peak areas were integrated to determine the total amount of beneficial agent extracted from each sample.

[0132] The beneficial agent leakage percentage is determined by calculating the difference obtained by subtracting the total amount of beneficial agent extracted from Sample 1 from the total amount of beneficial agent extracted from Sample 2, expressed as a percentage of the total amount of beneficial agent extracted from Sample 2, as shown in the following formula:

[0133]

[0134] Delivery particles can be prepared that exhibit a positive zeta potential. Such capsules have improved deposition efficiency, for example, on fabrics.

[0135] Sample preparation for biodegradability measurements

[0136] Water-soluble or water-dispersible materials were purified via crystallization until greater than 95% purity was achieved and dried prior to biodegradability measurements.

[0137] The oily medium containing the beneficial agent needs to be extracted from the delivery particle slurry in order to analyze only the polymer wall. Therefore, the delivery particle slurry is freeze-dried to obtain a powder. Then, it is further washed with an organic solvent via Soxhlet extraction to extract the oily medium containing the beneficial agent until the weight percentage of the oily medium based on the total delivery particle polymer wall is less than 5%. Finally, the polymer wall is dried and analyzed.

[0138] The weight ratio of delivery particles to solvent was 1:3. The residual oily medium was determined by thermogravimetric analysis (isothermal at 100°C for 60 minutes and at 250°C for another 60 minutes). The measured weight loss needed to be less than 5%.

[0139] leakage

[0140] The amount of beneficial agent leakage from the beneficial agent-containing delivery particles was determined according to the following method:

[0141] i) Obtain two 1 g samples of the stock slurry containing the delivery particles of the benefit agent.

[0142] ii) 1 g of the raw slurry of the delivery particles containing the benefit agent was added to 99 g of the consumer product base (where the particles were to be used) and the mixture was labeled Sample 1. A second 1 g sample of the raw particle slurry was used immediately in step d below in its pure form without contact with the consumer product base and was labeled Sample 2.

[0143] iii) The product matrix containing the delivery particles (Sample 1) was aged at 35°C in a sealed glass jar for 1 week.

[0144] iv) Particles were recovered from both samples using filtration. Particles in Sample 1 (in the consumer product matrix) were recovered after the aging step. Particles in Sample 2 (pure feedstock slurry) were recovered at the same time as the Sample 1 aging step was initiated.

[0145] v) treating the recovered particles with a solvent to extract the benefit agent material from the particles.

[0146] vi) analyzing via chromatography the solvent containing the beneficial agent extracted from each sample.

[0147] vii) The resulting benefit agent peak areas under the curves were integrated and the areas summed to determine the total amount of benefit agent extracted from each sample.

[0148] viii) The percentage of beneficial agent leakage is determined by calculating the difference obtained by subtracting the total amount of beneficial agent extracted from Sample 1 (S1) from the total amount of beneficial agent extracted from Sample 2 (S2), expressed as a percentage of the total amount of beneficial agent extracted from Sample 2 (S2), as shown in the following formula:

[0149]

[0150] Volume weighted median particle size

[0151] Particle size is measured using a static light scattering device such as an Accusizer 780A (manufactured by ParticleSizing Systems, Santa Barbara, California). The instrument is calibrated from 0 to 300μ using Duke particle size standards. Samples for particle size evaluation are prepared by diluting about 1 g of the emulsion if the volume weighted median particle size of the emulsion is to be determined, or 1 g of the delivery particle slurry containing the benefit agent if the volume weighted median particle size of the finished particles is to be determined, in about 5 g of deionized water, and further diluting about 1 g of this solution in about 25 g of water.

[0152] Add approximately 1 g of the maximum diluted sample to the Accusizer and start the test using the auto-dilution feature. The Accusizer should read over 9200 counts / second. If the count is less than 9200, additional sample should be added. The Accusizer will dilute the test sample until 9200 counts / second and begin evaluation. After 2 minutes of testing, the Accusizer will display the results, including the volume-weighted median size.

[0153] Methods of Olfactory Evaluation

[0154] After the fabrics have been treated, a professional perfumer makes an olfactory assessment of the dry fabric perfume intensity at the DRY contact point (Dry Fabric Odor = DFO), at the RUB contact point (Rubbed Fabric Odor = RFO; dry the fabric for a day, smell the fabric for DFO, then manually manipulate the fabric by rubbing the fabric against itself and smell the fabric again for RFO), and the scores are averaged. The scores are based on a perfume odor intensity scale from 0 to 100, where 0 = no perfume odor, 25 = slight perfume odor, 50 = medium perfume odor, 75 = strong perfume odor, and 100 = very strong perfume odor. "ΔRFO" may be reported, which is the difference between RFO and DFO.

[0155] The breadth index can be calculated by determining the particle size that accounts for more than 95% of the cumulative particle volume (95% size), the particle size that accounts for more than 5% of the cumulative particle volume (5% size), and the median particle size (50% size - 50% of the particle volume is above this size and 50% of the particle volume is below this size). Breadth index = ((95% size) - (5% size) / 50% size).

[0156] Method for determination of headspace concentration above treated dry fabrics

[0157] Cotton tracers were analyzed by a fast headspace GC / MS (gas chromatography mass spectrometry) method. 4×4 cm aliquots of towel cotton tracers were transferred to 25 ml headspace bottles. Fabric samples were equilibrated at 65°C for 10 minutes. The headspace above the fabric was sampled for 5 minutes via the SPME (50 / 30 μm DVB / Carboxen / PDMS) method. The SPME fiber was then thermally desorbed online into the GC. Analytes were analyzed by fast GC / MS in full scan mode. Specific mass ion extraction of PRMs was used to calculate the fragrance headspace composition and total HS response above the tested leg.

[0158] Unless otherwise indicated, all temperatures herein are in degrees Celsius (° C.) Unless otherwise indicated, all measurements herein are made at 20° C. and under atmospheric pressure.

[0159] Unless otherwise indicated, all percentages and ratios are calculated by weight. Unless otherwise indicated, all percentages and ratios are calculated based on the total composition.

[0160] It should be understood that each maximum numerical limit given throughout this specification includes each lower numerical limit, as if such lower numerical limits are explicitly written in this article. Each minimum numerical limit given throughout this specification will include each higher numerical limit, as if such higher numerical limits are explicitly written in this article. Each numerical range given throughout this specification will include each narrower numerical range that falls within such a wider numerical range, as if such a narrower numerical range is explicitly written in this article.

[0161] In the following examples, the abbreviations correspond to the materials listed in Table 1. The examples are intended to be illustrative in nature and are not intended to be limiting.

[0162] Table 1

[0163]

[0164] Example

[0165] The examples provided below are intended to be illustrative in nature and are not intended to be limiting.

[0166] Comparative Example 1.

[0167] The aqueous phase was prepared by dispersing 92.19 g of chitosan (ULV grade, Primex EHF, Siglufjordur, Iceland) in 1956.6 g of water while mixing in a jacketed reactor. The pH of the aqueous phase was then adjusted to 5.37 using 39.16 g of concentrated HCl (hydrochloric acid, 32-38%, Avantor Performance Materials, LLC, Radnor, PA) under stirring. The chitosan was then acid treated by increasing the temperature of the aqueous phase to 95° C. over 90 minutes and then maintaining it at 95° C. for a period of time (e.g., 2 hours). The aqueous phase temperature was then reduced to 25° C. over a period of 90 minutes after the acid treatment step.

[0168] The oil phase was prepared by mixing 716.36 g of fragrance oil and 179.10 g of isopropyl myristate (Acme-Hardesty Co., Bule Bell, PA) with 19.59 g of Takenate D-110N (Mitsui Chemicals America, Inc., RyeBrook, NY) at room temperature. The oil phase was added to the water phase under high shear grinding to obtain an emulsion. The emulsion was heated to 65° C. over 45 minutes and then to 85° C. over 60 minutes. The emulsion was then maintained at this temperature for 6 hours while mixing. The delivery particle population of the final slurry had a volume weighted median particle size of 28.84 microns.

[0169] Comparative Example 2.

[0170] The aqueous phase was prepared by dispersing 101.26 g of chitosan (ULV grade, Primex EHF, Siglufjordur, Iceland) in 2153.18 g of water while mixing in a jacketed reactor. 8.42 g of concentrated HCl (hydrochloric acid, 32-38%, Avantor Performance Materials, LLC, Radnor, PA) was then added to the chitosan mixture under stirring. The pH of the aqueous phase was then adjusted to 5.43 using 16.26 g of 90% formic acid (Brenntag Great Lakes, LLC, Wauwatosa, WI) under stirring. The chitosan was then acid treated by increasing the temperature of the aqueous phase to 95° C. over 90 minutes and then maintaining it at 95° C. for a period of time (e.g., 2 hours). The aqueous phase temperature was then reduced to 25° C. over a period of 90 minutes after the acid treatment step.

[0171] The oil phase was prepared by mixing 786.74 g of fragrance oil and 196.71 g of isopropyl myristate (Acme-Hardesty Co., Bule Bell, PA) with 21.53 g of Takenate D-110N (Mitsui Chemicals America, Inc., RyeBrook, NY) at room temperature. The oil phase was added to the water phase under high shear grinding to obtain an emulsion. The emulsion was heated to 65° C. over 45 minutes and then to 85° C. over 60 minutes. The emulsion was then maintained at this temperature for 6 hours while mixing. The delivery particle population of the final slurry had a volume weighted median particle size of 26.26 microns.

[0172] Comparative Example 3.

[0173] The aqueous phase was prepared by dispersing 12.35 pounds of chitosan (ULV brand, Primex EHF, Siglufjordur, Iceland) in 262.10 pounds of water while mixing in a jacketed tank. The pH of the aqueous phase was then adjusted to 5.19 using 2.7 pounds of 90% formic acid (Brenntag GreatLakes, LLC, Wauwatosa, WI) with stirring. The chitosan was then acid treated by increasing the temperature of the aqueous phase to 95° C. over 90 minutes and then maintaining it at 95° C. for a period of time (e.g., 2 hours). The aqueous phase temperature was then reduced to 25° C. over a period of 90 minutes after the acid treatment step.

[0174] The oil phase was prepared by mixing 78.2 pounds of fragrance oil and 42 pounds of isopropyl myristate (Acme-Hardesty Co., Bule Bell, PA) with 2.6 pounds of Takenate D-110N (Mitsui Chemicals America, Inc., Rye Brook, NY) in a jacketed tank at room temperature. The oil phase was added to the water phase under high shear grinding to obtain an emulsion. The emulsion was heated to 65° C. over 45 minutes and then to 85° C. over 60 minutes. The emulsion was then maintained at this temperature for 6 hours while mixing. The delivery particle population of the final slurry had a volume weighted median particle size of 32.11 microns.

[0175] Example 1.

[0176] The aqueous phase was prepared by dispersing 101.31 g of chitosan (ULV grade, Primex EHF, Siglufjordur, Iceland) in 2149.03 g of water while mixing in a jacketed reactor. 25.19 g of concentrated HCl (hydrochloric acid, 32-38%, Avantor Performance Materials, LLC, Radnor, PA) was then added to the chitosan mixture under stirring. The pH of the aqueous phase was then adjusted to 5.43 using 8.5 g of 90% formic acid (Brenntag Great Lakes, LLC, Wauwatosa, WI) under stirring. The chitosan was then acid treated by increasing the temperature of the aqueous phase to 95° C. over 90 minutes and then maintaining it at 95° C. for a period of time (e.g., 2 hours). The aqueous phase temperature was then reduced to 25° C. over a period of 90 minutes after the acid treatment step.

[0177] The oil phase was prepared by mixing 786.70 g of fragrance oil and 196.68 g of isopropyl myristate (Acme-Hardesty Co., Bule Bell, PA) with 21.57 g of Takenate D-110N (Mitsui Chemicals America, Inc., RyeBrook, NY) at room temperature. The oil phase was added to the water phase under high shear grinding to obtain an emulsion. The emulsion was heated to 65° C. over 45 minutes and then to 85° C. over 60 minutes. The emulsion was then maintained at this temperature for 6 hours while mixing. The delivery particle population of the final slurry had a volume weighted median particle size of 25.65 microns.

[0178] Example 2.

[0179] The aqueous phase was prepared by dispersing 12.31 pounds of chitosan (ULV grade, Primex EHF, Siglufjordur, Iceland) in 261.33 pounds of water while mixing in a jacketed tank. 3.07 pounds of concentrated HCl (hydrochloric acid, 32-38%, Avantor Performance Materials, LLC, Radnor, PA) was then added to the chitosan mixture under stirring. The pH of the aqueous phase was then adjusted to 5.22 using 1.11 pounds of 90% formic acid (Brenntag Great Lakes, LLC, Wauwatosa, WI) under stirring. The chitosan was then acid treated by increasing the temperature of the aqueous phase to 95° C. over 90 minutes and then maintaining it at 95° C. for a period of time (e.g., 2 hours). The aqueous phase temperature was then reduced to 25° C. over a period of 90 minutes after the acid treatment step.

[0180] The oil phase was prepared by mixing 95.68 pounds of fragrance oil and 23.92 pounds of isopropyl myristate (Acme-Hardesty Co., Bule Bell, PA) with 2.62 pounds of Takenate D-110N (Mitsui Chemicals America, Inc., Rye Brook, NY) in a jacketed tank at room temperature. The oil phase was added to the water phase under high shear grinding to obtain an emulsion. The emulsion was heated to 65°C in 45 minutes and then to 85°C in 60 minutes. The emulsion was then maintained at this temperature for 6 hours while mixing. The delivery particle population of the final slurry had a volume weighted median particle size of 28.82 microns. The degradable percentage of the shell was 63.42% at 60 days according to the 301B test.

[0181] Example 3.

[0182] The aqueous phase was prepared by dispersing 101.30 g of chitosan (ULV brand, Primex EHF, Siglufjordur, Iceland) in 2148.95 g of water while mixing in a jacketed reactor. 16.80 g of concentrated HCl (hydrochloric acid, 32-38%, Avantor Performance Materials, LLC, Radnor, PA) was then added to the chitosan mixture under stirring. The pH of the aqueous phase was then adjusted to 5.43 using 12.44 g of 90% formic acid (Brenntag Great Lakes, LLC, Wauwatosa, WI) under stirring. The chitosan was then acid treated by increasing the temperature of the aqueous phase to 95° C. over 90 minutes and then maintaining it at 95° C. for a period of time (e.g., 2 hours). The aqueous phase temperature was then reduced to 25° C. over a period of 90 minutes after the acid treatment step.

[0183] The oil phase was prepared by mixing 786.73 g of fragrance oil and 196.69 g of isopropyl myristate (Acme-Hardesty Co., Bule Bell, PA) with 21.56 g of Takenate D-110N (Mitsui Chemicals America, Inc., RyeBrook, NY) at room temperature. The oil phase was added to the water phase under high shear grinding to obtain an emulsion. The emulsion was heated to 65° C. over 45 minutes and then to 85° C. over 60 minutes. The emulsion was then maintained at this temperature for 6 hours while mixing. The delivery particle population of the final slurry had a volume weighted median particle size of 26.57 microns.

[0184] Example 4.

[0185] The aqueous phase was prepared by dispersing 101.26 g of chitosan (ULV grade, Primex EHF, Siglufjordur, Iceland) in 2149.6 g of water while mixing in a jacketed reactor. 25.22 g of concentrated HCl (hydrochloric acid, 32-38%, Avantor Performance Materials, LLC, Radnor, PA) was then added to the chitosan mixture under stirring. The pH of the aqueous phase was then adjusted to 5.45 using 24.34 g of 40% acetic acid (Columbus Chemical Industries, Inc, Columbus, WI) under stirring. The chitosan was then acid treated by increasing the temperature of the aqueous phase to 95° C. over 90 minutes and then maintaining it at 95° C. for a period of time (e.g., 2 hours). The aqueous phase temperature was then reduced to 25° C. over a period of 90 minutes after the acid treatment step.

[0186] The oil phase was prepared by mixing 786.71 g of fragrance oil and 196.68 g of isopropyl myristate (Acme-Hardesty Co., Bule Bell, PA) with 21.51 g of Takenate D-110N (Mitsui Chemicals America, Inc., RyeBrook, NY) at room temperature. The oil phase was added to the water phase under high shear grinding to obtain an emulsion. The emulsion was heated to 65° C. over 45 minutes and then to 85° C. over 60 minutes. The emulsion was then maintained at this temperature for 6 hours while mixing. The delivery particle population of the final slurry had a volume weighted median particle size of 30.93 microns.

[0187] Example 5.

[0188] The aqueous phase was prepared by dispersing 101.28 g of chitosan (ULV grade, Primex EHF, Siglufjordur, Iceland) in 2139.74 g of water while mixing in a jacketed reactor. 16.82 g of concentrated HCl (hydrochloric acid, 32-38%, Avantor Performance Materials, LLC, Radnor, PA) was then added to the chitosan mixture under stirring. The pH of the aqueous phase was then adjusted to 5.45 using 36.78 g of 40% acetic acid (Columbus Chemical Industries, Inc, Columbus, WI) under stirring. The chitosan was then acid treated by increasing the temperature of the aqueous phase to 95° C. over 90 minutes and then maintaining it at 95° C. for a period of time (e.g., 2 hours). The aqueous phase temperature was then reduced to 25° C. over a period of 90 minutes after the acid treatment step.

[0189] The oil phase was prepared by mixing 786.74 g of fragrance oil and 196.68 g of isopropyl myristate (Acme-Hardesty Co., Bule Bell, PA) with 21.51 g of Takenate D-110N (Mitsui Chemicals America, Inc., RyeBrook, NY) at room temperature. The oil phase was added to the water phase under high shear grinding to obtain an emulsion. The emulsion was heated to 65° C. over 45 minutes and then to 85° C. over 60 minutes. The emulsion was then maintained at this temperature for 6 hours while mixing. The delivery particle population of the final slurry had a volume weighted median particle size of 28.84 microns.

[0190] Example 6. Chitosan treated with a single acid

[0191] To compare the performance of delivery particles made from chitosan materials that were subjected to various treatments using a single acid, three populations of delivery particles were prepared.

[0192] Chitosan was treated with hydrochloric acid, formic acid and acetic acid, respectively. Fragrance delivery particles were prepared according to the present disclosure, wherein the shell was made of acid-treated chitosan and cross-linked with a polyisocyanate. The core of the delivery particle included, on average, about 80% of the first fragrance and about 20% of the partitioning modifier (i.e., isopropyl myristate). The volume weighted average particle size of the particle population was about 12 to 14 microns.

[0193] To test the freshness performance of the resulting delivery particles, samples of liquid fabric enhancer ("LFE") were prepared from the different delivery particles described above. The test LFE composition included about 6% by weight of diester quat. The chitosan-based delivery particles were present in the test LFE composition at a level that provided about 0.2% of the encapsulated fragrance by weight of the LFE composition. The pH of the test LFE composition was adjusted to about 3.

[0194] The fabrics were treated according to the fabric treatment method provided in the Test Methods section above. The fabrics were evaluated for dry fabric odor (DFO) and rubbed fabric odor (RFO) according to the olfactory evaluation method provided in the Test Methods section above. The results are provided in Table 2 below.

[0195] Additionally, a heavy-duty liquid (HDL) detergent matrix was provided with delivery particles and tested for leakage after one week of storage. The leakage percentages are provided in Table 2.

[0196] Table 2

[0197]

[0198] * = Comparative Example

[0199] As shown in Table 2, based on olfactory evaluation, delivery particles made from chitosan treated with weak acids (i.e., formic acid or acetic acid) provided comparable or even better freshness performance relative to delivery particles made from chitosan treated with strong acids (i.e., hydrochloric acid). It is also expected that weak acids will result in an improved corrosion profile for the associated slurries.

[0200] Interestingly, acetic acid appears to provide improved freshness performance compared to formic acid when providing delivery particles to LFE products. However, as shown in Table 2, particles made from chitosan treated with acetic acid exhibited relatively poor leakage profiles in HDL products compared to particles made from chitosan treated with formic acid. Additionally, it was noted that the particle slurry made from chitosan treated with acetic acid exhibited some gelation, which can lead to processing challenges.

[0201] Example 7. Effect of mixed acid treatment on the freshness performance of particles

[0202] In order to compare the freshness performance of delivery particles made from chitosan materials that were subjected to various acid treatments, samples of liquid fabric enhancer ("LFE") were prepared from the different delivery particles described above.

[0203] For each test, the core of the delivery particle included, on average, about 65%-80% of the secondary fragrance and about 20%-35% of the partitioning modifier (ie, isopropyl myristate).

[0204] Test LFE compositions were prepared having the general formulation as provided in Table 3. The chitosan-based delivery particles were present in the test LFE compositions at a level to provide approximately 0.2% of encapsulated flavor by weight of the LFE composition. The pH of the test LFE compositions was adjusted to approximately 3.

[0205] Table 3

[0206]

[0207] 1 N,N-bis(tallowoyloxyethyl)-N,N-dimethylammonium chloride, formerly Evonik

[0208] 2 Flosoft FS222, formerly SNF

[0209] The fabrics were treated according to the fabric treatment method provided in the Test Methods section above. The fabrics were evaluated for Dry Fabric Odor (DFO) and Rubbed Fabric Odor (RFO) according to the Olfactory Evaluation method provided in the Test Methods section above.

[0210] Formic acid

[0211] The results for capsules made from chitosan treated at least in part with formic acid are provided in Table 4 below.

[0212] Table 4

[0213]

[0214] * = Comparative Example

[0215] Based on the data in Table 4, delivery particles formed from chitosan treated with a mixed acid system (e.g., a strong:weak normality ratio from 80:20 to 20:80, where the weak acid is formic acid) provide comparable olfactory performance (e.g., RFO>50) relative to delivery particles formed from chitosan treated with HCl alone. However, due to the presence of the weak acid, it is believed that such a system will be relatively less corrosive.

[0216] The data in Table 4 also indicate that delivery particles made from chitosan treated with an acid system having relatively large amounts (eg, normality ratio less than 20:80) of formic acid (a weak acid) resulted in relatively poor performance (eg, RFO less than 46).

[0217] Acetic acid

[0218] The results for capsules made from chitosan treated at least in part with acetic acid are provided in Table 5 below.

[0219] Table 5

[0220]

[0221]

[0222] * = Comparative Example

[0223] Based on the data in Table 5, delivery particles formed from chitosan treated with a mixed acid system (e.g., a strong:weak normality ratio of 80:20 to 20:80, where the weak acid is acetic acid) provide comparable or even improved olfactory performance (e.g., RFO>50) relative to delivery particles formed from chitosan treated with HCl alone. However, due to the presence of the weak acid, it is believed that such a system will be relatively less corrosive.

[0224] Furthermore, in view of separate data collected by the applicant, it is believed that delivery particles formed from chitosan treated with only acetic acid are less preferred, for example, in terms of leakage from liquid detergent matrices.Thus, it is believed that the presence of a certain minimum level of strong acid (eg, HCl) is desirable for performance reasons.

[0225] Example 8. Effect of Slurry Chloride Level on Corrosion

[0226] The following test was run to examine the effect of chloride levels in the delivery particle slurry on the corrosion of stainless steel materials commonly used in manufacturing equipment.

[0227] Chitosan was treated with formic acid and used to prepare fragrance delivery particles according to the methods described in the present disclosure. Samples of the resulting particle slurry were doped with magnesium chloride (MgCl2) in order to provide slurries with different chloride levels.

[0228] Stainless steel coupons (grade = 316L SS; dimensions = 3 / 4" x 2" x 1 / 8", with a 120 grit sanded finish) were placed in trays at approximately 38°C and subjected to a wet / dry test, which involved periodically wetting the coupons with the slurry sample over a twenty-eight day period (i.e., immersion on the first day and then every seven days). At the end of the treatment, the coupons were inspected for pitting due to corrosion. The total number of pitting on the coupons before and after was counted and reported in Table 6 below.

[0229] Table 6

[0230]

[0231] * = Comparative Example

[0232] As shown in Table 6, relatively small amounts of chloride ions in the slurry resulted in less pitting, indicating less corrosion. Based on the data in Table 6, slurries with chloride levels less than 0.4% are preferred, with levels less than 0.2% being even more preferred.

[0233] The capsules according to the invention may have a core to wall ratio of even up to 95 wt % core to 1 wt % wall. In applications where enhanced degradability is desired, higher core to wall ratios may be used, for example 99 wt % core to 1 wt % wall, or even 99.5 wt % to 0.5 wt % or higher. With appropriate choice of the core to wall ratio, the shell of the composition according to the invention may be selected to achieve the following % degradation when tested according to test method OECD 301B: at least 40% degradation after 28 days, and at least 60% degradation after at least 60 days.

[0234] Unless otherwise indicated herein or clearly contradictory to the context, the use of the singular "a", "an" is intended to cover both the singular and the plural. The terms "comprising", "having", "including" and "containing" are interpreted as open terms. All references cited herein (including publications, patent applications and patents) are incorporated herein by reference. Any description of some embodiments as "preferred" embodiments and other descriptions of embodiments, features or ranges as preferred or these are preferred suggestions are not considered to be limiting. The invention is considered to include embodiments that are currently considered less preferred and can be described as such herein. Unless otherwise indicated herein or clearly contradictory to the context, all methods described herein can be performed in any suitable order. Any and all examples or exemplary language (e.g., "for example") provided herein are intended to illustrate the present invention, rather than to impose limitations on the scope of the invention. Any statements herein about the attributes or benefits of the present invention or preferred embodiments are not intended to be limiting. The present invention includes all modifications and equivalents of the subject matter recorded herein as permitted by applicable law. In addition, unless otherwise indicated herein or clearly contradictory to the context, the present invention includes any combination of the above-described elements with all possible variations thereof. The description herein of any reference or patent, even if identified as "existing", is not intended to constitute an admission that such reference or patent is available as prior art against the present invention. Unclaimed language should not be construed as limiting the scope of the present invention. Any statement or suggestion herein that some feature constitutes a claimed component of the present invention is not intended to be limiting unless reflected in the appended claims.

Claims

1. A composition comprising a population of delivery particles, wherein the delivery particle comprises a core and a shell surrounding the core, wherein the core comprises a benefit agent, wherein the shell comprises a polymeric material which is the reaction product of acid-treated chitosan and a cross-linking agent, wherein the acid-treated chitosan is produced by treating chitosan with a mixture of a first acid and a second acid, The first acid comprises a strong acid, The second acid comprises a weak acid, wherein the first acid and the second acid are present in an equivalent concentration ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35, wherein the chitosan is treated with the mixture at a pH of 6.5 or less and at a temperature of at least 25°C.

2. The composition of claim 1, wherein the first acid comprises a strong acid selected from the group consisting of hydrochloric acid, perchloric acid, nitric acid, sulfuric acid, and mixtures thereof.

3. The composition of claim 1, wherein the second acid comprises an organic acid selected from the group consisting of formic acid, acetic acid, ascorbic acid, glutamic acid, lactic acid, maleic acid, malic acid, succinic acid, citric acid, succinic acid, citric acid, acrylic acid, oxalic acid, tartaric acid, and mixtures thereof.

4. The composition of claim 1, the first acid having a first pKa of less than 1, and the second acid having a first pKa of about 1-5.

5.

5. The composition of claim 1, wherein the chitosan is characterized by a weight average molecular weight of about 100 kDa to about 600 kDa, preferably about 100 kDa to about 500 kDa, more preferably about 100 kDa to about 400 kDa, more preferably about 100 kDa to about 300 kDa, even more preferably about 100 kDa to about 200 kDa.

6. The composition of claim 1, wherein the first acid and the second acid are each independently selected from the group consisting of a monoacid, a diacid, and a polyacid.

7. The composition of claim 1, wherein the ratio of the crosslinking agent to the acid-treated chitosan is from 79:21 to 10:90, or even from 2:1 to 1:8, or even from 1:1 to 1:7, based on weight.

8. The composition of claim 1, wherein the shell comprises up to 25% by weight of the core-shell encapsulate.

9. The composition of claim 1, wherein the crosslinking agent is a polyisocyanate selected from the group consisting of polyisocyanurates of toluene diisocyanate, trimethylolpropane adducts of toluene diisocyanate, trimethylolpropane adducts of xylylene diisocyanate, methylene diphenyl diisocyanate, toluene diisocyanate, tetramethylxylidine diisocyanate, naphthalene-1,5-diisocyanate, phenylene diisocyanate, 2,2'-methylene diphenyl diisocyanate, 4,4'-methylene diphenyl diisocyanate, 2,4'-methylene diphenyl diisocyanate, tetramethylxylidine diisocyanate, naphthalene-1,5-diisocyanate, 1,4-phenylene diisocyanate, 1,3-diisocyanatobenzene, and combinations thereof.

10. The composition of claim 1, wherein the shell degrades by at least 40% after at least 60 days when tested according to test method OECD 301B.

11. The composition of claim 1, wherein at least 21% by weight of the shell consists of moieties derived from the acid-treated chitosan.

12. The composition of claim 1, wherein the core-shell encapsulate has a core to shell ratio of at least 75:25, or at least 99:1, or even at least 99.5:0.5 by weight.

13. The composition of claim 1, wherein the benefit agent is selected from the group consisting of fragrances, scents, agricultural actives, phase change materials, essential oils, lubricants, colorants, preservatives, antimicrobial actives, antifungal actives, herbicides, antiviral actives, preservative actives, antioxidants, bioactives, deodorants, emollients, moisturizers, exfoliants, UV absorbers, corrosion inhibitors, silicone oils, waxes, bleaching particles, fabric conditioners, malodor reducing agents, dyes, optical brighteners, antiperspirant actives, and mixtures thereof.

14. The composition of claim 1, wherein the delivery particles have a median particle size of 1-200 microns.

15. The composition of claim 1, wherein the encapsulate is cationic.

16. The composition of claim 1, wherein the encapsulate has a zeta potential of at least 1 mV at pH 4.

5.

17. The composition of claim 1, wherein the shell degrades by at least 60% of its mass after at least 60 days when tested according to test method OECD 301B.

18. The composition of claim 1, wherein the benefit agent is a fragrance, preferably the fragrance comprises a perfume raw material characterized by a logP of about 2.5 to about 4.

5.

19. The composition of claim 1, wherein the core further comprises a partition modifier selected from the group consisting of isopropyl myristate, vegetable oils, modified vegetable oils, mono-, di- and triesters of C4-C24 fatty acids, lauryl benzophenone, lauryl laurate, methyl behenate, methyl laurate, methyl palmitate, methyl stearate, and mixtures thereof, preferably isopropyl myristate.

20. The composition according to claim 1, wherein the shell has a biodegradability of greater than 30% CO2, preferably greater than 40% CO2, more preferably greater than 50% CO2, even more preferably greater than 60% CO2 (maximum 95%) within 60 days when tested according to test method OECD 301B.

21. A method for preparing a population of delivery particles, wherein the delivery particle comprises a core and a shell surrounding the core, wherein the core comprises a benefit agent, Wherein the shell comprises a polymeric material which is a reaction product of acid-treated chitosan and a cross-linking agent, the method comprising: forming an aqueous phase by treating chitosan with a mixture of a first acid and a second acid, the first acid comprising a strong acid and the second acid comprising a weak acid, wherein the chitosan is treated at a pH of 6.5 or less, or even less than pH 6.0, or even at a pH of 3-6 and at a temperature of at least 25° C., and wherein the first acid and the second acid are present in a normality ratio of about 20:80 to about 80:20, preferably about 35:65 to about 65:35, and thereby forming acid-treated chitosan; forming an oil phase comprising dissolving together at least one benefit agent and at least one polyisocyanate, optionally with added oil; forming an emulsion by: mixing the aqueous phase and the oil phase in an excess of the aqueous phase, thereby forming droplets of the oil phase, the droplets being dispersed in the aqueous phase, and optionally adjusting the pH of the emulsion to within the range of pH 3-pH 6; curing the emulsion at a temperature of at least 40° C. for a time sufficient to form a shell at the interface of the droplet with the aqueous phase, the shell comprising the reaction product of the polyisocyanate and the acid-treated chitosan, and surrounding the core, the core comprising the droplet of the oil phase, wherein at least 21 wt% of the shell comprises the acid-treated chitosan.

22. The method of claim 21, wherein the chitosan is treated with a mixture of a first acid and a second acid in the aqueous phase for a duration and at a temperature to achieve a viscosity of the aqueous phase of 1500 cps or less, preferably less than 500 cps, more preferably 50 to 300 cps.

23. An article of manufacture comprising a delivery particle according to any one of the preceding claims.

24. The article of manufacture of claim 23, wherein the article is selected from the group consisting of an agricultural formulation, a slurry encapsulating an agricultural active agent, a population of dried encapsulates encapsulating an agricultural active agent, an agricultural formulation encapsulating a pesticide, and an agricultural formulation for delivery of a pre-emergent herbicide.

25. The article of manufacture of claim 24, wherein the agriculturally active agent is selected from the group consisting of agricultural herbicides, agricultural pheromones, agricultural pesticides, agricultural nutrients, insect control agents, and plant stimulants.

Citation Information

Patent Citations

  • Delivery particle

    US20110268802A1

  • Method and system for pinpointing the location of an electronic device

    US20200252469A1

  • Manifold record material

    US2730456A

  • Oil-containing microscopic capsules and method of making them

    US2800457A

  • Oil-containing microscopic capsules and method of making them

    US2800458A